(untitled) (Quaestiones Disputatae: temas en debate, 2018)
The article of reﬂection approaches the beginning and development of Capitalism, of some essential ideas of its fundaments and questionings, in economic, historical, political and cultural aspects, in the world and particularly in Latin America and Colombia. The main authors and ideas are taken into account both for their defense and their criticism. The purpose of this paper is to provide a brief, quick and essential reading of the origin and development of capitalism, presenting its intellectual leaders and also its internal and external contractors, so that the reader has an overview and can thus form a better awareness and attitude about the two conceptions that are presented here. It attempts to analyze its progress and its limitations as a socio-economic formation, which is subsequent to Feudalism and prior to Socialism. The analyzes presented are part of the academic and scientiﬁc exercise for the debate on the subject, in this era of a new global crisis.